Uso de residuos sólidos en la elaboración de concreto celular: una revisión - Muñóz Perez, Sócrates Pedro (2021)
Millions of tons of different types of waste are generated each year worldwide and this is expected to increase in the future. Most of this waste is dumped through landfills or incineration, raising major environmental concerns. An alternative for the reuse of these wastes is to incorporate them as partial or total replacements for the components of cellular concrete. In this regard, aerated concrete could provide an excellent means of incorporating these residues in a large volume mainly due to the low strength requirement. Cellular concrete is classified into two types based on its manufacturing method, the air entrainment method and the foaming method. Therefore, this document collects and reviews the use of various types of waste, such as industrial solid waste and agricultural solid waste, as a potential replacement for cement, fine aggregate or foaming agent in aerated concrete. and foamed. Each type of waste contributes differently to the performance of cellular concrete; generally incorporating the waste materials can produce a cellular concrete with low density, with an increase in the compressive strength and improvements in the thermal insulation properties.